Recycling, Norms, and Convenience: A Bivariate Probit Analysis of Household Data From a Swedish City - Berglund, Christer; Söderholm, Patrik; Hage, Olle (Frontiers in Sustainable Cities, 2022)
The purpose of this paper is to investigate the role of norms and convenience for households’ packaging waste sorting activities. The theoretical point of departure is an existing model that integrates norm-motivated behavior into neoclassical utility theory by assuming that the individual has a preference for maintaining a self-image as a morally responsible (norm-compliant) person. The empirical analysis rests on survey responses from 398 households in the city of Eskilstuna, Sweden. elf-reported information on recycling contributions and personal norms is analyzed in a bivariate probit model, which estimates the probability of pursuing high-performing recycling efforts as an endogenously determined decisions to the activation of a personal norm for waste sorting. The results suggest that norm activation is an important driver for households’ recycling contributions, as is convenience in the form of access to property-close collection schemes. Personal norms are in turn primarily activated by the presence of social, legal, and descriptive norms. One important policy implication is that policy often need to build on well-aligned policy instruments mixes that combine references to the moral significance of household’ recycling contribution with various infrastructural measures that facilitate such contribution.